Ideologi dalam pesan paskah 2023: pendekatan analisis wacana kritis dengan model Fairclough - Kabanga, Lewi; Tabuni, Simon; Kalangi, Ayu Nangsi (Universitas Mulawarman, 2023)
Easter is one of the significant moments for Christians and Catholics. The purpose of this study is to understand the texts containing ideology by the Indonesian Communion of Churches (PGI) and the Archdiocese of Jakarta of 2023. The method applied was qualitative descriptive with data collection techniques, namely documentation by downloading written texts from PGI and the Archdiocese of Jakarta. Then downloaded data was followed by data reduction and displayed processes. The results of this process were analyzed using a Critical Discourse Analysis approach with Fairclough's model, which includes Textual, discursive, and socio-cultural analysis. The results of this study show that the textual dimension reveals linguistic features such as fundamentalist and contextual interpretation, cause-and-effect features, and connotative words that undergo expanded meanings. In addition to these features, the use of the pronoun “we” emphasizes the equal positions, indicating strategy of emphasis persuasive meaning. The discursive practices show the variety of language features such as repetition and borrowing texts, Meanwhile, the socio-cultural dimension reveals the concerns and anticipatory attitudes toward potential threats such as the Covid-19 pandemic, global recession, political wars, political issues in 2024, social justice and welfare system, and the consumptive attitude.